Application of (AHP) Multicriteria Hierarchical Analysis for the Acquisition Analysis of a Thermobalance - Romo-Nava, María (2024)
Decision making is essential throughout life and this depends on the success or failure of the actions or responses taken when difficulty arises, for which the tool AHP (Analytic Hierarchy Process) is a discrete multicriteria method that considers qualitative and quantitative aspects. The tool was considered in this project to analyze the decision of acquiring a thermobalance for an educational institution’s academic activities. The purchasing department took into account the users’ needs and considerations from experts based on functionality. For this reason, the method gave us the best decision.